Rancang Bangun Sistem Informasi Keuangan Pada CV.Tiga Mestika Berbasis Website - Setiawan, Adam; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2022)
Tiga Mestika was established on October 18, 2007, CV Tiga Mestika is located on Jl Pulau Komodo No 21 Denpasar. Based on the results of interviews, there are problems that occur in the company's operations, in particular, the financial statements produced are not accurate, the impact is that there are often errors in writing financial data by admins. In addition, the archiving of records of sales and purchase notes is recorded manually causing an incorrect cash book. properly archived, so that checking reports on the cash book is difficult to do every year. Based on the description of the problems contained in CV. Tiga Mestika, a computerized financial reporting system is needed to facilitate the work on CV. Three Jewels. This information system will be able to minimize the risk of errors in managing financial statements, bookkeeping records will also become more accurate and make it easier to find data quickly when needed so as to be able to provide better service to customers or consumers. Based on the problems that occur in the company, the authors create a system, namely